Aṡar al-Bī’ah al-Lughawiyyah ‘alā Raghbah al-Talāmiż fī Ta’alum al-Lughah al-‘Arabiyyah - Moh In'ami; Fathima Azzahra; Dahmani Chourouk (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAIN Kudus, 2021)
The school environment is the first environment for students to learn the Arabic language. The school environment affects the students' desire to learn Arabic. The aim of this study is to know the impact of the school environment on the students' desire to learn Arabic in Rawdat Al-Subyan Secondary School. And the type of research means field research with the quantitative research approach. The results of this research show that the impact of the school environment in the secondary school kindergarten boys in the category of